N6-methyladenosine could indirectly modulate translation in human cancer cells via cis-elements - Zhang, Yongchun; Chen, Zhiying; Zhang, Lijian; Jiang, Peng; Li, Wei (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: N6-methyladenosine (m6A) is one of the common forms of RNA modifications. METTL3 is the essential factor that has methyltransferase activity. One important role of m6A is to regulate translation of mRNAs via reader YTHDF1. However, whether m6A could indirectly affect the translation of mRNA through other approaches remains unclear. Methods: We retrieved the m6A genes in HeLa cells generated by a previous study. In the METTL3 or YTHDF1 knock-down libraries, we examined the global changes in mRNA splicing as well as translation efficiency (TE). Results: In, METTL3-KD cells, the differential splicing (DS) genes are enriched in m6A modified genes. The DS events are relatively enriched in 5'UTR of mRNAs. The 105 genes with DS events in 5'UTR alter their TE more strongly than the genes with DS events in other regions (CDS/3'UTR/intron). Furthermore, the splicing pattern of 98 out of those 105 genes are unaffected by reader YTHDF1. Importantly, we did not observe significant TE changes for these 98 genes when YTHDF1 was knocked down. Conclusions: In HeLa cells, for a small set of genes, m6A could modulate the translation of modified mRNAs through affecting the splicing patterns. These indirect effects are independent of the direct regulation by reader proteins as we have verified using YTHDF1-KD data. This pattern is likely caused by the gain or loss of cis-elements in 5'UTRs that determine the translation of host genes. Our work extended our knowledge about the translation regulation by m6A.